2010
DOI: 10.1186/cc8965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of earplugs and eye masks on nocturnal sleep, melatonin and cortisol in a simulated intensive care unit environment

Abstract: IntroductionEnvironmental stimulus, especially noise and light, is thought to disrupt sleep in patients in the intensive care unit (ICU). This study aimed to determine the physiological and psychological effects of ICU noise and light, and of earplugs and eye masks, used in these conditions in healthy subjects.MethodsFourteen subjects underwent polysomnography under four conditions: adaptation, baseline, exposure to recorded ICU noise and light (NL), and NL plus use of earplugs and eye masks (NLEE). Urine was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
156
5
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(179 citation statements)
references
References 33 publications
12
156
5
6
Order By: Relevance
“…Half of the studies assessed the effect of using the earplug or eyemask intervention for only 1 night, [11][12][13] whereas the others evaluated use for up to 5 nights. 5,[8][9][10] Sleep was predominantly measured through self-report of sleep quality/quantity, as well as factors that prevented and promoted reported psychometrics. One study measured sleep variables objectively by using polysomnography in a simulated critical care environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the studies assessed the effect of using the earplug or eyemask intervention for only 1 night, [11][12][13] whereas the others evaluated use for up to 5 nights. 5,[8][9][10] Sleep was predominantly measured through self-report of sleep quality/quantity, as well as factors that prevented and promoted reported psychometrics. One study measured sleep variables objectively by using polysomnography in a simulated critical care environment.…”
Section: Methodsmentioning
confidence: 99%
“…5,[9][10][11]13 One investigation used the Verran-SynderHalpern Sleep Scale, 12 whereas others used the Richards-Campbell Sleep Questionnaire 10 or the Sleep Assessment Tool, 13 the latter of which has no …”
Section: About the Authorsmentioning
confidence: 99%
“…In this study, it was found that patients in both groups had a mild level of state anxiety before application and a moderate level of state anxiety after application. In a study by Hu et al (2010), the mean state anxiety level before the application of earplugs and eye masks was found to be 32.5 ± 5.6, and after the application of earplugs and eye masks it was found to be 29.8 ± 6.4. In a study by Jones and Dawson (2012), 60% of patients in the experimental group and only 2% of patients in the control group defined state anxiety as a factor which prevented them from sleeping [32].…”
Section: Anxietymentioning
confidence: 96%
“…They found that the mean score for sleep quality was 10.78 ± 4.78 as measured by PSQI [36]. A study by Hu et al (2010) examined the effect of earplugs and eye masks on sleep; and the mean PSQI score for nights when the earplugs and eye masks were not used was found to be 4.1 ± 1.7, and for nights when the earplugs and eye masks were used it was found to be 2.3 ± 1.3 [31,34]. In a study by Yalçın Atar et al (2012) with 107 patients from a surgery clinic, it was found that the sleep quality of 55.1% of patients was poor according to the PSQI.…”
Section: Mean Sleep Pointsmentioning
confidence: 99%
See 1 more Smart Citation